2017
DOI: 10.1136/bmjgh-2016-000147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the global financial crisis on low birth weight in Portugal: a time-trend analysis

Abstract: BackgroundThe 2007–2008 global financial crisis had adverse consequences on population health of affected European countries. Few contemporary studies have studied its effect on perinatal indicators with long-lasting influence on adult health. Therefore, in this study, we investigated the impact of the 2007–2008 global financial crisis on low birth weight (LBW) in Portugal.MethodsData on 2 045 155 singleton births of 1995–2014 were obtained from Statistics Portugal. Joinpoint regression analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 45 publications
5
49
0
3
Order By: Relevance
“…Contemporary evidence indicates that as socio‐economic conditions worsen in host country, there is an upsurge in the prevalence of adverse pregnancy outcomes among immigrants . The universal health care and perinatal health system instituted in Portugal for over two decades has contributed in improving pregnancy outcomes irrespective of maternal nativity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary evidence indicates that as socio‐economic conditions worsen in host country, there is an upsurge in the prevalence of adverse pregnancy outcomes among immigrants . The universal health care and perinatal health system instituted in Portugal for over two decades has contributed in improving pregnancy outcomes irrespective of maternal nativity .…”
Section: Resultsmentioning
confidence: 99%
“…The rate of adverse pregnancy outcomes could be influenced by period variation in demographic, economic, and social structure of the society or condition of the maternal population including access to health care . In Portugal, the 2007‐2008 global financial crisis was associated with a significant increase in LBW, particularly among infants of non‐Portuguese mothers . It was observed that the financial crisis and austerity measures were associated with household food insecurity, poor health outcomes, and affected health care access .…”
Section: Introductionmentioning
confidence: 99%
“…Para identificar alterações na tendência (joinpoint) 42 da taxa de suicídio e estimar a variação relativa média anual em cada um dos períodos identificados no arco temporal de 1980 a 2015 foi aplicado um modelo de regressão log-linear. A análise começa com o número mínimo de joinpoints e testa se a inclusão de novos joinpoints é estatisticamente significativa.…”
Section: Métodosunclassified
“…Os autores declaram que os procedimentos seguidos estavam de acordo com os regulamentos estabelecidos pelos responsáveis da Comissão de Investigação Clínica [38][39][40][41][42][43][44] e Ética e de acordo com a Declaração de Helsínquia da Associação Médica Mundial.…”
Section: Protecção De Pessoas E Animaisunclassified
See 1 more Smart Citation